2021
DOI: 10.35414/akufemubid.889289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cut-outs on the Free Vibration Response of Basalt/Carbon Hybrid Composites

Abstract: The current work deals with an experimental investigation about the influence of cut-outs on dynamic characteristics of basalt/carbon hybrid fiber reinforced composite laminates. The composite samples have been fabricated via vacuum assisted resin transfer molding technique and cut-outs in the form of triangular, square and circular shapes with equal areas have been processed on them to systematically analyze the influences of cut-outs. The dynamic characteristics of the samples have been examined by conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…% nano‐silica and without cutout were seen as 22.9% and 8.75% for the specimens having circular and semicircular cutouts, respectively. Özbek and Tokur Bozkurt 55 reported that cutouts had a negative impact on the vibration characteristics of the basalt/carbon hybrid composites due to the reductions in stiffness.…”
Section: Resultsmentioning
confidence: 99%
“…% nano‐silica and without cutout were seen as 22.9% and 8.75% for the specimens having circular and semicircular cutouts, respectively. Özbek and Tokur Bozkurt 55 reported that cutouts had a negative impact on the vibration characteristics of the basalt/carbon hybrid composites due to the reductions in stiffness.…”
Section: Resultsmentioning
confidence: 99%